Depression, social phobia and quality of life after major lower limb amputation - Tutak, Yılmaz; Şahin, İlhami; Demirtaş, Abdullah; Azboy, İbrahim; Özkul, Emin; Gem, Mehmet; Adıyeke, Levent (Haydarpaşa Numune Eğitim ve Araştırma Hastanesi, 2020)
Introduction: In this study, we aimed to compare the social phobia, depression and quality of life in patients with major lower limb amputation to non-amputated.Methods: Patients who were underwent above or below the knee amputation in the past were evaluated retrospectively by examining the hospital records. All the participants were administered Liebowitz Social Anxiety Scale (LSAS), Hospital Anxiety and Depression Scale (HADS), and Short-Form 36 (SF-36).Results: The number of patients was 30 (21 males, nine females) in the amputated group and 30 (22 males, eight females) in the control group. The mean age was 41.8±14.09 years in the amputated group and 43.3±18.68 years in the control group. All LSAS and HADS scores were higher, and SF-36 scores were lower in the amputation group compared to the control group (p<0.05). The patients who were amputated more than five years ago had higher LSAS social fear scores, and lower HAD depression scores compared to patients less than five years (p=0.035, p=0.024, respectively). The employed patients had lower HAD depression and HAD total scores compared to unemployed patients (p=0.008, p=0,049, respectively). The patients amputated due to medical complications had higher scores in anxiety compared to the patients with traumatic amputation (p=0.005, p=0.016, respectively).Discussion and Conclusion: Social phobia, depression and poor quality of life are common problems in patients with major lower limb amputation. After five years, it should not be forgotten that social phobia will increase; depression will decrease along with its seriousness. Therefore, amputated patients should be psychiatrically counseled and treated. It is important to provide permanent employment opportunities to improve the quality of life.
Keywords: Amputation; Social Phobia; Depression; Quality of Life; Psychiatry